The effectiveness of the Think Pair Share (TPS) method on explanatory text writing skills in terms of learning styles - Yolani Erawati; Syahrul Ramadhan (Universitas Ahmad Dahlan, 2021)
This study aims to review the effectiveness of the think pair share method on explanatory text writing skills in terms of learning styles. This type of research is quantitative with the 2x2 factorial experimental method. The population in this study were eighth grade students of SMP Negeri 1 Kinali. Research data was collected using a questionnaire and performance test. Based on the results of data analysis, it can be concluded that (1) the explanatory text writing skills of students who study using the think pair share method are higher than students who study using conventional methods, (2) the explanatory text writing skills of students who have high learning styles who study with the think pair share method are higher than students who learn by conventional methods, (3) the explanatory text writing skills of students who have low learning styles who study with the think pair share method are higher than students who learn by conventional methods, and (4) there is an interaction between the think pair share method and learning styles in influencing the skills of writing explanatory texts.